Perbandingan Emisi CO2 Menggunakan Beton dan Aspal - Marpaung, Ridwan (Jurnal Sosial Ekonomi Pekerjaan Umum, 2014)
Indonesia is one of the countries that signed Kyoto Protocol to reduce greenhouse gas emission in 1997. Road construction sector contributes 15% CO2 emission of the entire sectors, where most of the 39% is contributed by the national road. In Indonesia, the usage of concrete road tends to replace the asphalt road to anticipate overload and over capacity of the road due to the traffic and also at the poor drainage condition. But the comparison of CO2 emission contributed by the both roads is not known. The aim of the research is to compare the amount CO2 emission and to determine the econonic saving cost or economic loss caused by its emission. The data were collected from contract document and deep interview. Using life cycle assessment method of 10 years, concrete road usage will cause loss at 1,162.5 tCO2e/km or 19,763.18$ /tCO2e/km, but in 20 years will save 661.2 tCO2e/km or 11,237$./tCO2/km, with emission ratio 1:1,22 and cost efffectiveness 16,1$/tCO2/km. The most CO2 emission contribution from concrete road is the extraction and production phase (85,4%) especially from cement material, while for asphalt road at construction phase give 51,0% especially from heavy duty equipment usage.